Analysis of drafting effects in swimming using computational fluid dynamics - Silva, A. J.; Rouboa, A.; Moreira, A.; Machado Reis, V.; Alves, F.; Vilas-Boas, J. P.; Almeida Marinho, D. (Journal of Sports Science & Medicine, 2008)
The purpose of this study was to determine the effect of drafting distance on the drag coefficient in swimming. A k-epsilon turbulent model was implemented in the commercial code Fluent® and applied to the fluid flow around two swimmers in a drafting situation. Numerical simulations were conducted for various distances between swimmers (0.5-8.0 m) and swimming velocities (1.6-2.0 m.s-1). Drag coefficient (Cd) was computed for each one of the distances and velocities. We found that the drag coefficient of the leading swimmer decreased as the flow velocity increased. The relative drag coefficient of the back swimmer was lower (about 56% of the leading swimmer) for the smallest inter-swimmer distance (0.5 m). This value increased progressively until the distance between swimmers reached 6.0 m, where the relative drag coefficient of the back swimmer was about 84% of the leading swimmer. The results indicated that the Cd of the back swimmer was equal to that of the leading swimmer at distances ranging from 6.45 to 8. 90 m. We conclude that these distances allow the swimmers to be in the same hydrodynamic conditions during training and competitions.